Ecological Awareness and Behavior in Poland: The Results of the 2021 Research - Jakub DONSKI-LESIUK; Joanna GORNIAK (Communications of International Proceedings, 2021)
The aim of the paper is to analyze and evaluate the awareness and ecological behavior of Poles in the light of empirical research conducted in 2021. This article identifies examples of ecological activities and assesses the reasons of its undertaking. Several factors that are a manifestation of ecological behavior were focused in more detail, namely: forms of waste disposal, attitude to the form of packaging, as well as to its use and possible return (and / or willingness to return), paying attention to actions ecological undertaken by enterprises. Some recommendations that could contribute to increasing environmental awareness in the future have also be indicated as conclusions from the conducted study.
Keywords: Consumer behavior analysis; diagnosis of contemporary ecological attitudes; individual decision; behavior survey research